INTEGRATING RENEWABLE ENERGY AND SMART GRID SYSTEMS: A PATHWAY TO CARBON-NEUTRAL COMMUNITIES IN SOUTHEAST ASIA - Putra, Yogi; Furqan, Furqan (International Journal of Multidisciplinary Research and Literature, 2026)
The transition toward carbon-neutral communities has become a global priority, especially in Southeast Asia, where rapid economic growth continues to intensify energy use and carbon emissions. Although the region has substantial renewable energy potential, it remains highly dependent on fossil fuels due to weak grid infrastructure, limited digitalization, and inconsistent policy support. This study systematically synthesizes recent scientific research on the role of smart grid technologies and renewable energy integration in supporting the development of carbon-neutral communities. Using a Systematic Literature Review (SLR) approach guided by PRISMA, 24 peer-reviewed Scopus articles published between 2017 and 2023 were analyzed. The selected literature met predetermined inclusion and exclusion criteria and focused on renewable energy adoption, smart grid deployment, and low-carbon community initiatives. The review identifies five major theoretical foundations frequently used in contemporary research: Energy Transition Theory, Smart Grid Theory, Diffusion of Innovation Theory, Resilience Theory, and Socio-Technical Systems Theory. Evidence consistently shows that smart grids powered by IoT, digital automation, advanced metering, and sensor technologies enhance energy efficiency, load management, grid stability, and the integration of renewable sources. The analysis further highlights that socio technical conditions, innovation characteristics, digital readiness, policy frameworks, and community participation significantly shape the adoption of renewable technologies. However, empirical studies remain unevenly distributed, with limited research focusing specifically on rural or tourism-based communities in Southeast Asia. To address these gaps, this study proposes a comprehensive conceptual model that integrates renewable energy, smart grid systems, and socio-technical enablers to support the advancement of carbon-neutral communities.